The role of typical and atypical pathogens in acute exacerbations of chronic obstructive pulmonary disease. (24th October 2020) - Yildiz, Sevilay; Gonullu, Nevriye; Yildiz, Birsen Pinar; Hattatoglu, Didem Gorgun; Kuskucu, Mert; Midilli, Kenan; Aygun, Gokhan; Mayda, Pelin Yuksel; Musellim, Benan
Abstract: Objectives: The exact role of Mycoplasma pneumoniae, Chlamydophila pneumoniae, and Legionella pneumophila in the development of chronic obstructive pulmonary disease exacerbations remains to be elucidated. This study was conducted to identify nonspecific and atypical pathogens associated with acute exacerbations of COPD. Materials and Methods: Between February 2013 and February 2015, 107 patients were analyzed. Sixty‐nine comprised the inpatient and 38 comprised the outpatient treatment group. Results: When nonspecific culture results were taken into consideration only a causative organism could be detected in 46.7% of the patients. The detection rate increased to 85.1% with the additional use of polymerase chain reaction (PCR), direct fluorescent antibody (DFA) test, and culture methods. More than one causative agent was responsible for COPD exacerbation in 53.3% of patients: two agents in 37.3%, three agents in 15%, and four agents in 0.9%. H. influenzae was detected in 63 (58.9%) patients, S. pneumoniae in 57 (53.2%), P. aeruginosa in 15 (14.0%), and L. pneumophila in 11 (10%). L. pneumophila was the more commonly isolated agent in the inpatient group ( P = 0.002). Patients receiving continuous oxygen therapy and noninvasive mechanical ventilation were more likely to have an exacerbation associated with P. aeruginosa ( P = 0.008 and P = 0.009, respectively). Conclusion: The additional use of DFA for Legionella and multiplex PCR in combination with nonspecific microbiological culturing methods greatly improves the ability to identify infectious agents in acute exacerbations of COPD. There should be a high index of suspicion for P.aeruginosa as a causative organism, particularly in subjects receiving continuous oxygen therapy and/or using NIV and L. pneumophila should certainly be taken into consideration in severe COPD exacerbations.